(untitled) (Bangladesh Journal of Zoology, 2022)
Dengue is one of the most prevalent mosquito-borne viral disease worldwide which is transmitted to humans by infected female Aedes mosquitoes. Bangladesh has become a suitable habitat for the vector of dengue and is struggling with dreadful outbreaks in recent years. This study used social media as a tool to conduct a survey with a detailed questionnaire on the prevalence of Dengue and knowledge, attitude, and practices (KAP) on Dengue transmission during 2020 COVID-19 outbreak. Out of 234 participants, prevalence of dengue was 21.37% with high prevalence of dengue fever (18.80%) followed by dengue hemorrhagic fever (2.14%) and dengue shock syndrome (0.43%). The highest prevalence was observed in people aged 21 to 30 years (11.54%). Male participants had higher prevalence (11.97%) compared to female (9.4%). Prevalence was 5.13% in Dhaka North City Corporation compared to 14.10% in Dhaka South City Corporation. The prevalence was highest in people with monthly income above 30000 BDT (9.40%). Prevalence of dengue was 18.38% for those who used mosquito repellents vs 2.99% those who didn’t use. Prevalence was 6.84% in those who had plants in tub, 3.85% with an indoor garden and 0.85% with bush. Only 11.97% remembered seeing any awareness campaigns, 94.44% knew how dengue was transmitted, 97.86% correctly mentioned the name of the vector. Alarmingly, only 65.81% answered correctly about the diurnal nature of Aedes and 53.42% responded that COVID-19 has affected the diagnosis and treatment of Dengue. Bangladesh J. Zool. 49 (3): 355-367, 2021